Prototipe Penyiram Tanaman Dan Pengukur Kelembaban Tanah Berbasis Arduino Uno - Hamid Muhammad Jumasa; Wahju Tjahjo Saputro (Universitas Muhammadiyah Purworejo, 2019)
Agricultural land is currently increasingly narrow, so agricultural technology develops hydroponic crop models. The microcontroller in the Arduino UNO unit is also growing so that the Internet of Things technology is increasingly rapid and widely used in life. The problem of narrow land used for plants requires soil moisture as needed. This can be solved using Arduino UNO as a data acquisition system and the YL-69 sensor as a soil moisture reading tool.This study aims to implement the YL-69 sensor and Arduino UNO to detect whether the soil media used in the hydroponic plant model is moist or dry. The sketch used is Arduino 1.8.0 software. Then the Fritzing software is used to create a circuit schema. The series tests were performed on both dry and wet soil conditions. This research was in the form of a watering plant prototype. When the dry media is detected, the sensor will send data to the Arduino UNO unit, then the microcontroller on the Arduino UNO gives instructions to the Mini Submersible Water Pump to irrigate the soil.The results showed the YL-69 sensor was able to detect dry soil conditions. Data sent to the serial monitor is in the form of a data string that is